L'individu dans l'organisation: les dimensions oubliées - Gaha, Chiha (Relations industrielles / Industrial Relations, 1991)
The aticle reviews the book, "L'individu dans l'organisation: les dimensions oubliées," edited by J.F. Chanlat.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z